Israel’s Foreign Policy Interests in Normalizing Relations with Middle East Countries - Rio Sundari; Suyastri, Cifebrima; Prayuda, Rendi; Rani, Faisyal (Program Studi Ilmu Pemerintahan Fakultas Ilmu Sosial dan Ilmu Politik Universitas Maritim Raja Ali Haji, 2023)
This research aims to explain Israel's foreign policy interests in normalizing relations with Arab countries. Between 2020 and 2021, Israel concluded normalization agreements with 4 Arab countries (United Arab Emirates, Bahrain, Sudan, Morocco) announced and mediated by President Trump. Previously, in 1978, Egypt had already normalized relations with Israel by signing a peace agreement mediated by then US leader Jimmy Carter. In 1994, Jordan also followed in Egypt's footsteps to normalize relations with Israel in the Washington Declaration mediated by Bill Clinton. This research uses a descriptive qualitative research model approach in analyzed problems empirically. The qualitative approach used in this research is a type of literature study whose data sources are analyzed from books, journals and news protals that have a correlation with the research. The results of the study mentioned that the shift in the perspective of regional security to interests allowed the normalization of this relationship. However, this development does not mean that this normalization leads to peace and stability as the main goal. On the contrary, this diplomatic relationship is only an ulterior motive in carrying out interest mutualism to gain benefits, international status and global reputation that are more favorable to Israel.